Sentidos Que Le Ortorgan Las Practicantes De Fútbol A La Motivación En Las Relaciones De Pareja Con Relación A Los Procesos Deportivos (2014)
This work shows a study about the senses that the practitioners of football professional team of Santiago de Cali "Cali Junior's" motivation gives in relation to the sports process; the objective of this study was to reveal the senses granted by the members of that community, identifying the relationships between behavior and the concepts expressed by them; determining the sporty performance in relation to the motivation. Where conducted an analysis that is exposed by an interview with depth and a guide of observation to determine the existing factors of motivation of the players; found senses are three macro categories and seven subcategories composed of different motivational attitudes, from different theoretical positions and theories substantive exposed by the women interviewed. They participated in the study (interview) 4 athletes; the conclusions of this, revolve around the work carried out by the athletes, and the possible implications of motivation in the development of its sports